Old, to some gold – pepper or the fruit as spice - Jutta, Mariam (University Putra Malaysia, 2012)
Pepper - the oldest and still most important culinary condiment known to man. Of the 1,200 species of Piper, a genus native to the tropics, around 400 have been recorded from Malesia. Piper nigrum, the most commonly cultivated, is native to India. Pepper was brought to South-east Asia by Hindu monks around 2000 years ago. In the Middle Ages, P. nigrum and Chilli peppers slowly replaced other types of pepper.